Pelatihan Teknik Dasar Dan Sosialisasi Permainan Gateball pada Pengcab PERGATSI Kota Bukittinggi - Roma Irawan; Padli Padli; Ronni Yenes; Eko Noresha (Jurnal Berkarya Pengabdian Masyarakat, 2020)
Bukittinggi city is one of the tourist destinations that various types of activity offers in it, one of which is an effort to foster sports achievements and recreational sports. One of the sports that benefits from the location of this geograpis is the sports game Gateball. The sport was recently developed in the city and the organization was recently confirmed as a member of KONI Bukittinggi City. Gateball sports game is a game by inserting the ball into the goal using a stick. Gateball is played on a rectangular field measuring 15 x 20 meters, while the game time lasts for 30 minutes. Therefore, it is necessary to socialize and training techniques for administrators, prospective coaches and athletes. The design of the mechanism of implementation of this activity is carried out by measures consisting of the stage of planning activities with the board, then the process of the activity is carried out by the method of lectures and demonstrations. After the activity, further observation and evaluation is carried out to see the progress of the results of this training. From this activity can be obtained the following objectives;1) The administrators understand the concept of performance in running an organization with managerial support for the progress of this Gateball rganization. 2) Gateball coaches with training skills and experience supported by the application of science and technology. Conclusion in this activity, it is expected that the administrators collaborate with coaches to maximize the application of sports science studies to upset gateball sports and give birth to athletes in Bukittinggi city specifically and for west Sumatra province in general in various National and International championships